2002
DOI: 10.7202/004864ar
|View full text |Cite
|
Sign up to set email alerts
|

Varve, paleomagnetic, and 14 C Chronologies for late Pleistocene events in New Hampshire and Vermont (U.S.A.)

Abstract: A deglacial chronology for northern New England has been formulated using an atmospheric 14 C calibration of the New England Varve Chronology and paleomagnetic records. This 14 C chronology is based on 14 C ages from macrofossils of non-aquatic plants and is about 1 500 yr younger than existing chronologies that are based primarily on 14 C ages of bulk organic samples. The lower and upper Connecticut Valley varve sequences of Ernst Antevs (NE varves 2 701-6 352 and 6 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 78 publications
3
30
0
2
Order By: Relevance
“…Water level changes in the Hudson basin associated with the drainage routing of glacial lakes Iroquois, Vermont, and Albany between ∼11,300 and 10,900 14 C year BP (Licciardi et al, 1999;Clark et al, 2001;Rayburn et al, 2005) may have precipitated dam failure at the Narrows. The most likely time interval for breaching of the moraine dam at the Narrows is between 12,300 14 C year BP (Ridge, 1997;Licciardi et al, 1999) and the initiation of the Champlain Sea at about 11,100 14 C year BP (Rodrigues, 1988;Ridge et al, 1999;Richard and Occhietti, 2005). Recently, Donnelly et al (2005) suggested an age of ∼ 11,450 14 C year BP (∼13,350 cal BP) for the flood event.…”
Section: Glacial Drainage and Timing Of The Meltwater Floodmentioning
confidence: 99%
“…Water level changes in the Hudson basin associated with the drainage routing of glacial lakes Iroquois, Vermont, and Albany between ∼11,300 and 10,900 14 C year BP (Licciardi et al, 1999;Clark et al, 2001;Rayburn et al, 2005) may have precipitated dam failure at the Narrows. The most likely time interval for breaching of the moraine dam at the Narrows is between 12,300 14 C year BP (Ridge, 1997;Licciardi et al, 1999) and the initiation of the Champlain Sea at about 11,100 14 C year BP (Rodrigues, 1988;Ridge et al, 1999;Richard and Occhietti, 2005). Recently, Donnelly et al (2005) suggested an age of ∼ 11,450 14 C year BP (∼13,350 cal BP) for the flood event.…”
Section: Glacial Drainage and Timing Of The Meltwater Floodmentioning
confidence: 99%
“…Ridge pinpointed the readvance age much more precisely and confirmed the Older Dryas connection through his work on the New England Varve Chronology and its relation to the Comerford Dam readvance site. His varve correlations in the Connecticut River valley west of Littleton showed that the readvance occurred at 11,900-11,800 14 C ka BP (13.9-13.8 cal ka BP) (Ridge et al, 1999. The Lake Hitchcock varve chronology is now incorporated in the North American Varve Chronology of .…”
Section: Previous Workmentioning
confidence: 99%
“…Ridge pinpointed the readvance age much more precisely and confirmed the Older Dryas connection through his work on the New England Varve Chronology and its relation to the Comerford Dam readvance site. His varve correlations in the Connecticut River valley west of Littleton showed that the readvance occurred at 11, 800 14 C ka BP (13.9-13.8 cal ka BP) (Ridge et al, 1999(Ridge et al, , 2004. The Lake Hitchcock varve chronology is now incorporated in the North American Varve Chronology of Ridge et al (2012).…”
Section: Figurementioning
confidence: 99%